Training Young Russian Physicians in Uganda: A Unique Program for Introducing Global Health Education in Russia - Bulat A. Ziganshin (Ubiquity Press, 2016)
Background: Global health is a new concept in Russia. There has been an ongoing academic collaboration between the Yale School of Medicine in the United States and Makerere University College of Health Sciences in Uganda since 2010, and the US Western Connecticut Health Network/University of Vermont College of Medicine since 2012, to introduce global health concepts to Kazan State Medical University (KSMU) in Russia. The purpose was to educate Russian physicians and medical trainees about the practice of clinical medicine and medical education, as well as the general practice of global health in culturally diverse, resource-limited settings. Objectives: The aim of this study was to evaluate the initial outcomes of this multi-institutional partnership and to assess the impact of the global health elective on the participants and on KSMU. Methods: Participants were selected to attend a 6-week elective in global health at Mulago Hospital in Kampala, Uganda. The elective consisted of clinical experience, education about Uganda's common diseases, and region-specific sociocultural classes. It included a predeparture orientation and, upon return, completion of a standard questionnaire to assess the program's impact. Results: Since 2010, there have been 20 KSMU members (4 medical students, 4 interns, 9 residents, 2 fellows, and 1 faculty member) who have participated in the program. As a result of the elective, the participants reported increased knowledge of tropical medicine (70%) and HIV/AIDS (75%), and 95% reported increased cultural sensitivity and desire to work with the underserved. The majority noted a very positive impact of their careers (90%) and personal life (80%). KSMU established the first successful collaborative program in global health education in Russia, leading to the integration of tropical medicine and global health courses in medical school curriculum. Conclusion: This elective has proven highly effective in introducing the concept of global health to faculty, fellows, residents, and medical students at KSMU. It trained these participants to address the challenges faced by physicians in culturally diverse and resource-limited countries.